The Role of Hydrogeological Monitoring in a Multidisciplinary Context for the Preservation of the Critical Zone in the Natural Reserve of Castelporziano Estate - Sbarbati, Chiara; Lacchini, Alessandro; Petitta, Marco (Frontiers in Earth Science, 2022)
Critical Zone (CZ) science has developed in recent years, involving different disciplines that vary depending on the specific research focus. This multidisciplinary approach highlights the relevance of the Underground component of the Critical Zone (UCZ) in regulating the water cycle, which can influence the complex equilibrium of the whole CZ. In this study, we analyze evolution during the time of different parameters, characterizing the saturated and unsaturated parts of the UCZ of the Castelporziano Estate, a natural reserve located in a coastal area close to Rome. The purposes of these activities are to monitor the potential depletion of groundwater resources and understand the recharge mechanism processes characterizing the aquifer in the framework of occurring climate changes, net of anthropogenic pressure. The long-term analyses of water table variations carried out over the last 25 years, allowed us to preliminarily identify four different ranges of the slope coefficient of the water table, characterizing different areas of the Estate. Specifically, the Northern, Central, and Coastal areas have shown a general depletion trend in piezometric levels, while in the Eastern area, a positive trend has been recognized. Additional long-term analysis of piezometric level variations allowed us to confirm the presence of the four recharge areas and compare annual recharge and water table levels to assess the relationship between the saturated UCZ and meteoric recharge in the identified areas. To evaluate the role of the unsaturated UCZ in recharge mechanisms, the water content in the first meter of soil has also been analyzed, showing different responses of outcropping sediments in capturing rainfall during different periods of the year and under different rainfall input conditions, highlighting the pivotal role of rainfall for the Castelporziano UCZ, both for deep recharge of the water table and for feeding the forest roots. Stable isotopes confirm that Castelporziano UCZ feeding is strongly dependent on local meteoric recharge, also highlighting that evaporation processes are active in a limited way. The obtained results assess that the monitoring of UCZ has a crucial role in the correct preservation of more complex environmental systems, which include groundwater resources and the coastal Mediterranean forest.